A quantitative interpretation of the entry section of the EPPO decision‐support scheme for pest risk analysis. (17th December 2013) - Holt, J.; van der Gaag, D. J.; Leach, A. W.; MacLeod, A.; Baker, R. H. A.; Mumford, J. D.
Abstract : The development of methods to combine components of risk and their associated uncertainty in Pest Risk Analysis (PRA) has received attention in a number of recent European projects. Many of the risk components distinguished in the EPPO Decision‐support scheme (DSS) for PRA are usually difficult to quantify, but when there is detailed knowledge of the pest and pathway, quantification may be possible to a limited extent for the pest entry section of the scheme. The European Food Safety Authority has recently commissioned a project to investigate approaches to quantitative pathway analysis for pests of commodities entering and moving within the EU (QPA‐Food); a sister project concerns non‐food commodities. This paper illustrates the potential for a quantitative pathway model based closely on the Entry Section of the EPPO DSS for PRA, where existing quantitative definitions of rating categories have been used as a basis to estimate the proportion and number of infested lots on a pathway. Such quantification may provide additional insights without requiring substantial changes to the information elicited via the DSS.